ΒIV-Spectrin Autoantibodies in 2 Individuals With Neuropathy of Possible Paraneoplastic Origin: A Case Series. Issue 4 (17th July 2022) - Bartley, Christopher M.; Ngo, Thomas T.; Alvarenga, Bonny D.; Kung, Andrew F.; Teliska, Lindsay H.; Sy, Michael; DeRisi, Joseph L.; Rasband, Matthew N.; Pittock, Sean J.; Dubey, Divyanshu; Wilson, Michael R.; Pleasure, Samuel J.
Abstract : Objective: To identify the autoantigen in 2 individuals with possible seronegative paraneoplastic neuropathy. Methods: Serum and CSF were screened by tissue-based assay and panned for candidate autoantibodies by phage display immunoprecipitation sequencing (PhIP-Seq). The candidate antigen was validated by immunostaining knockout tissue and HEK 293T cell-based assay. Results: Case 1 presented with gait instability, distal lower extremity numbness, and paresthesias after a recent diagnosis of serous uterine and fallopian carcinoma. Case 2 had a remote history of breast adenocarcinoma and presented with gait instability, distal lower extremity numbness, and paresthesias that progressed to generalized weakness. CSF and serum from both patients immunostained the axon initial segment (AIS) and node of Ranvier (NoR) of mice and enriched βIV-spectrin by PhIP-Seq. Patient CSF and serum failed to immunostain NoRs in dorsal root sensory neurons from βI/βIV-deficient mice. βIV-spectrin autoantibodies were confirmed by overexpression of AIS and nodal βIV-spectrin isoforms Σ1 and Σ6 by a cell-based assay. βIV-spectrin was not enriched in a combined 4, 815 PhIP-Seq screens of healthy and other neurologic disease patients. Discussion: Therefore, βIV-spectrin autoantibodies may be a marker of paraneoplastic neuropathy. Classification of Evidence: This study provides Class IV evidence that βIV-spectrin antibodies are specific autoantibody biomarkers for paraneoplastic neuropathy.